INTENSITAS PENGGUNAAN ELECTRONIC BANKING OLEH NASABAH PT. BANK CENTRAL ASIA CABANG UTAMA AMBON - Pary, Gilman (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
The purpose of this research is to test the effect of consumers value and system quality toward trust in order to increase frequency of the use of internet banking. The sample in this research are 180 BCA consumer as respondent. The technique used in this research was purposive sampling. Certain characteristics means only for consumer whose at least  one  product  connected  with  electronic  banking  facility  and  using  electronic banking  facility  in  financial  and  non  financial  transaction  for  above  6  months. Structural Equation Modelling (SEM) run by AMOS software, used to analyze the data. The analysis result shows that consumer value and system quality effected on trust in order to increase the use of internet banking. This empirical result indicates that  consumers  value  have  significant  effect  toward  trust,  system  quality  have significant toward trust, and trust have significant toward the use of internet banking.